Evaluation of paraffin wax and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) blend patch for tissue engineering. (28th January 2021) - Yıldırım, Meryem Akkurt; Demirbilek, Murat; Türkoğlu, Nelisa
ABSTRACT: In the study, we aimed to develop a multipurpose tissue patch for the repairment of various tissue defects. Poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) was blended with paraffin wax, and the chemical composition of the membranes was determined by the FTIR and RAMAN spectroscopy. The surface area of the PHBHHx and PHBHHx/Paraffin wax were determined as (38, 79 m 2 /g) and (81, 108 m 2 /g), respectively. The DMA and DSC results revealed that blending with paraffin wax, increased the percentage of elongation of the PHBHHx membrane by 7, 6% and reduced the modulus of elasticity. While the elongation at break of PHBHHx tissue patch was 22, 463% (standard error = ± 2, 476), addition of Paraffin wax increased the value to 30, 038% (standard error = ± 7, 228). The antioxidant capacity significantly increased and p53/TP53 levels decreased after blending with paraffin. In conclusion, PHBHHx/paraffin wax blend patches can be considered as a promising biomaterial due to their high cell adhesion capacity depending on its increased surface area, fine anti-oxidant properties, and appropriate mechanical properties.